Perlindungan Hukum Masyarakat Adat di Wilayah Pertambangan (Lex Jurnalica, 2013)
AbstractThe operations of the mining region of indigenous people in recent decades caused quite a variety of issues considered to adversely affect the interests of indigenous people, so interesting to study more about the legal protection of indigenous peoples in the management of mining and the role of State to provide protection and welfare of indigenous peoples in mining areas. The research specification is analytical descriptive with normative juridic approach. Data analytical and conclusion of the research use qualitative method and will be presented in analytical descriptive. The rights of indigenous peoples have the constitutional basis and a solid legal basis, the provisions of Article 18B paragraph (2) Constitution in 1945, which regulates that: